(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This study aims to assess the effect of focal median nerve injury in patients with carpal tunnel syndrome ( CTS ) on F-wave of median and ulnar nerves, determine the importance of F-wave inversion in the patients with mild CTS and find out the effect of increasing body mass index (BMI) on median nerve and its association with the severity of CTS. The study was conducted in neurophysiological unit at Merjan Medical City, in the period from September 2015 to March 2016. Including (139) patient with clinical presentation of CTS as well as positive NCS with age ranged from (20-60) years. The study also includes(139) apparently healthy person as a control group of which were matched in age, gender and BMI to patients group. F-wave of median, ulnar and median-ulnar nerve difference are highly significant (p <0.01) in patients than control group. There is a significant association between mean median F wave minimal latency (FWML) and severity of CTS as most severe cases have higher mean. There is a significant relationship between F- wave inversions in mild CTS as compared to control group. Body mass index acts as an independent risk factor to develop CTS and most of patients with CTS are obese and overweight. There is a significant association between BMI and severity of CTS and most cases with mild, moderate and severe are obese (P < 0.05). The electrophysiological findings of sensory and motor parameters of median nerve including (latency, amplitude and conduction velocity) between patients and control groups all show highly significant difference (p <0.01).